2007
DOI: 10.1007/bf03033989
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional evaluation of systolic and distolic left ventricular temporal parameters using a novel program for ECG-gated myocardial perfusion SPECT

Abstract: The feasibility of evaluating systolic and diastolic temporal parameters by a new program was validated. This program has the potential to evaluate both diastolic and systolic heterogeneous wall motions which express dyssynchrony in heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Tissue velocity imaging and speckle tracking radial strain are also relatively new techniques that require a learning curve and hands-on training, because a certain level of experience is essential (53). Strain data are sensitive to the placement of the region of interest and require higher-quality images than the routine optical interpretation (53,54). Mavinkurve et al recently showed that myocardial strain and strain rate were significantly lower in survivors of childhood cancer than in healthy controls (55).…”
Section: Noninvasive Imaging Of Cardiotoxicitymentioning
confidence: 99%
“…Tissue velocity imaging and speckle tracking radial strain are also relatively new techniques that require a learning curve and hands-on training, because a certain level of experience is essential (53). Strain data are sensitive to the placement of the region of interest and require higher-quality images than the routine optical interpretation (53,54). Mavinkurve et al recently showed that myocardial strain and strain rate were significantly lower in survivors of childhood cancer than in healthy controls (55).…”
Section: Noninvasive Imaging Of Cardiotoxicitymentioning
confidence: 99%
“…We have validated the systolic/diastolic temporal indices obtained by cardioGRAF by comparing them with those obtained by ERNA and STI. 24 With regard to the systolic synchronous indices, MD-TES and MD-TPE in the G-C subjects were not different from those obtained from G-1 patients (Figs 6A,B). By contrast, the diastolic synchronous indices, MD-TPF1 and MD-TPF2 were significantly smaller in G-C subjects than in G-1 patients (Figs 6C,D).…”
Section: Systolic and Diastolic Dyssynchronymentioning
confidence: 61%
“…We have developed the new GMPS analyzing program to evaluate LV functional and temporal parameters globally and regionally. It has been validated in previous studies [7,8].…”
Section: Discussionmentioning
confidence: 91%
“…We developed GMPS analyzing program which evaluates not only global (g-) but also regional (r-) functional and temporal parameters including TPF [7,8]. It facilitates estimation of regional diastolic impairment by the elongation of r-TPF.…”
Section: Introductionmentioning
confidence: 99%